Solar and geothermal energy [ - Tabak, John (New York : Facts On File, 2009)
Describes a brief history of solar and geothermal energy, the way they are used and why they are two of the best sources of power for the environment
1. pt. I: Solar energy. A brief history of solar power -- 2. Sunlight and geometry -- 3. Photovoltaics -- 4. Heat engines and solar power -- 5. Two other important solar technologies -- 6. Economic and environmental consequences of solar power -- 7. Government policies and solar energy -- 8. pt. II: Geothermal energy. A brief history of geothermal energy -- 9. Geology and heat -- 10. The generating station -- 11. Two other geothermal technologies -- 12. The economics and environmental impacts of electricity from geothermal sources -- 13. Government policies and geothermal energy -- 14. Chronology -- 15. List of acronyms
Description based on print version record
Includes bibliographical references (p 188-192) and index
Keywords: Renewable energy source -- Juvenile literature